Russia and South Africa: Historical Memory. Part 2 - ARKHANGELSKAYA Alexandra Alexandrovna; SIDOROV Vasily Alexandrovich; TURIANITSA Daria Andreevna; SHUBIN Vladimir Gennadevich (Ученые записки Института Африки Российской академии наук)
This part of a joint article contains a survey of the sources regarding the history of cooperation between the Soviet Union and the national liberation movement in South Africa in the Russian central archives. The main ones are the Russian State Archive of Modern History, the State Archive of the Russian Federation, the Russian State Archive of Social and Political History, the Russian State Archive of the Economy and the Archive of Foreign Policy of the Russian Federation.